A benchmark dataset to advance heliosphere research.
Visible-light imagining of the heliosphere has revolutionised the study of solar wind by adding to in situ measurements. Building on this advance, European space scientists are combining their expertise to generate unique catalogues and advance our understanding of the whole Sun-to-Earth system.